Intolerance of uncertainty and anxiety as explanatory frameworks for extreme demand avoidance in children and adolescents. Issue 2 (22nd May 2019) - Stuart, Lisa; Grahame, Victoria; Honey, Emma; Freeston, Mark
Abstract : Background: Pathological demand avoidance (PDA) is a proposed subtype of autism spectrum disorder (ASD), characterised by extreme avoidance of demands. Demand avoidant behaviour has been proposed to be driven by an anxious need to be in control, although has never been explicitly studied. Emerging evidence suggests intolerance of uncertainty (IU) and anxiety may explain the behaviours seen in ASD. We propose these concepts may be useful starting points for furthering understanding of PDA. Methods: In Study 1, quantitative methods examined the relationship between PDA, IU and anxiety using data collected in an online survey ( N = 214). The sample included cases with clinically diagnosed PDA ( n = 69) and those with no clinical diagnosis but parent‐identified features of PDA ( n = 151). 'Children with a diagnosis of PDA scored significantly higher on the IUS‐P (t(212) = 2.45, p < .05) compared to those without a diagnosis of PDA. PDA diagnosis did not impact on scores on any other measure.' In Study 2, a selection of Study 1 participants ( n = 11) were followed up with a telephone interview to gain descriptive data relating to PDA and its association with IU and anxiety. Results: Regression analyses indicate that demand avoidant behaviour can be conceptualised in part as a possible attempt to increase certainty and predictability to alleviate increasing anxiety. Children and young people with PDA employed varying strategies to manage IU depending on the level of demand presented and degree of anxiety generated. These strategies can be represented by different features of the behaviour profile seen in PDA ( control behaviour, withdrawal to fantasy, and meltdown ). These behavioural features of PDA showed differential relationships with IU and anxiety, although all were predicted by IU, only meltdown demonstrated a mediation effect by anxiety. Conclusions: This study represents one of the first attempts to conceptualise and understand the behavioural features of the PDA profile in children and young people. It builds upon emerging evidence from the ASD literature that IU is a relevant construct for conceptualising demand avoidant behaviour in children who show PDA behaviour. This has potential clinical implications for the assessment and management of PDA in children and young people. Abstract : Read the Commentary on this article at doi: 10.1111/camh.12368